Harmonic transfer characteristics of MMC‐HVDC systems. Issue 13 (19th January 2018) - Rong, Li; Jun, Wen; Ruoxi, Liu; Han, Yan; Kangsheng, Cui
Abstract : Modular multilevel converter (MMC) is considered as the most potential development of multilevel converter, the future of high‐voltage electric energy conversion, especially in the high‐voltage direct current (HVDC) transmission since the very beginning because of its unmatched advantages such as high modularity, compact structure, high quality of output waveform, and common DC bus. However, due to the structural characteristics of the MMC itself, there will be circulating current that cannot be eliminated but suppressed in the arm, causing AC/DC‐side harmonic. Here, the authors first analyse the circuit topology, working principle, and characteristics of the MMC. The coupling relationship of MMC is studied by using the switching function method in the modulation theory, to facilitate rigorous analysis of the interrelationship between the harmonic and circulating current of MMC and the influencing factors of the harmonic from the analytical point of view. The influence of the harmonic generated by the MMC converter on the AC/DC side can be obtained by derivation. Moreover, the transfer mechanism of the background harmonic coming from AC system is further studied. Furthermore, the foregoing conclusions on harmonic transfer characteristics of MMC‐HVDC system are verified by using the simulation model built on PSCAD/EMTDC.